Tuning electrocatalytic activity of Pt monolayer shell by bimetallic Ir-M (M=Fe, Co, Ni or Cu) cores for the oxygen reduction reaction. (November 2016) - Kuttiyiel, Kurian A.; Choi, YongMan; Sasaki, Kotaro; Su, Dong; Hwang, Sun-Mi; Yim, Sung-Dae; Yang, Tae-Hyun; Park, Gu-Gon; Adzic, Radoslav R.
Abstract: Platinum monolayer electrocatalyst are known to exhibit excellent oxygen reduction reaction (ORR) activity depending on the type of substrate used. Here we demonstrate a relationship between the ORR electrocatalytic activity and the surface electronic structure of Pt monolayer shell induced by various IrM bimetallic cores (M=Fe, Co, Ni or Cu). The relationship is rationalized by comparing density functional theory calculations and experimental results. For an efficient Pt monolayer electrocatalyst, the core should induce sufficient contraction to the Pt shell leading to a downshift of thed -band center with respect to the Fermi level. Depending on the structure of the IrM, relative to that of pure Ir, this interaction not only alters the electronic and geometric structure but also induces segregation effects. Combined these effects significantly enhance the ORR activities of the Pt monolayer shell on bimetallic Ir cores electrocatalysts. Graphical abstract: Highlights: Core-shell structured IrM nanoparticles are better substrates than alloyed counterparts for Pt monolayer electrocatalyst. Geometric, electronic, and segregation effects together are crucial to understand the increase in ORR activity. DFT calculations demonstrate a volcano type behavior with PtML IrNi/C at the top of the curve.